Energy Harvesting System with Multiple Inputs. (August 2019) - Setyawati, O; Taufik,; Satriya, A
Abstract: Energy scavenging system that can harvest from multiple energy sources has been considered and remains a promising research topic. This paper presents characterization of a multiple input energy harvesting system for Wireless Sensor Network and evaluation of battery state of charge utilized in the system. The system under study automatically selects the highest voltage value from among connected harvested energy sources to determine which of the multiple sources will supply energy to charge the system's battery and any operating load. By means of the coulomb counting method in the wireless application board and under the regulated maximum input voltage of the application board of 3.3 V, the state of charge (SOC) of the system battery was observed to study the functionality and effectiveness of the multiple input energy harvesting system. Further hardware test results show approximately 0.013% of SOC is obtained.